Innovative molecular intervention and precision therapy for atherosclerosis - Wang, Zhijie; Peng, Wei; Huang, Linsheng; Zhang, Yan; Yang, Jie; Chen, Xiaolin; Liu, Xiang; Li, Feifeng; Zhang, Qiong (Frontiers in Cardiovascular Medicine, 2025)
Atherosclerosis is a chronic vascular disorder characterized by the pathological accumulation of lipids, inflammatory cells, and extracellular matrix within arterial walls. With the escalating global incidence of atherosclerosis, the development of more effective therapeutic interventions has emerged as a critical priority in biomedical research. Conventional treatment modalities, encompassing pharmacological agents and, endovascular interventions, have demonstrated partial efficacy in disease management. However, their clinical utility remains constrained by suboptimal therapeutic outcomes, treatment-related adverse effects, and instances of therapeutic failure. In response to these limitations, contemporary research has shifted focus toward novel therapeutic strategies targeting molecular pathways and immunomodulatory mechanisms, aiming to achieve enhanced precision and efficacy. This review synthesizes recent innovations in atherosclerosis therapeutics. Notable advancements include PCSK9 inhibitors and next-generation lipid-modulating agents, which have shown significant promise in clinical trials by achieving substantial reductions in atherogenic lipoprotein levels. Gene-editing technologies, particularly CRISPR-based approaches, exhibit potential for halting disease progression through targeted modulation of pro-atherogenic genes. Furthermore, emerging insights into the regulatory role of microRNAs in atherosclerotic plaque formation and instability have positioned miRNA-based therapeutics as a compelling frontier in precision medicine for cardiovascular diseases.